Total Body Irradiation or Chemotherapy Conditioning in Childhood ALL: A Multinational, Randomized, Noninferiority Phase III Study. Issue 4 (1st February 2021) - Peters, Christina; Dalle, Jean-Hugues; Locatelli, Franco; Poetschger, Ulrike; Sedlacek, Petr; Buechner, Jochen; Shaw, Peter J.; Staciuk, Raquel; Ifversen, Marianne; Pichler, Herbert; Vettenranta, Kim; Svec, Peter; et al.
Abstract : PURPOSE: Total body irradiation (TBI) before allogeneic hematopoietic stem cell transplantation (HSCT) in pediatric patients with acute lymphoblastic leukemia (ALL) is efficacious, but long-term side effects are concerning. We investigated whether preparative combination chemotherapy could replace TBI in such patients. PATIENTS AND METHODS: FORUM is a randomized, controlled, open-label, international, multicenter, phase III, noninferiority study. Patients ≤ 18 years at diagnosis, 4-21 years at HSCT, in complete remission pre-HSCT, and with an HLA-compatible related or unrelated donor were randomly assigned to myeloablative conditioning with fractionated 12 Gy TBI and etoposide versus fludarabine, thiotepa, and either busulfan or treosulfan. The noninferiority margin was 8%. With 1, 000 patients randomly assigned in 5 years, 2-year minimum follow-up, and one-sided alpha of 5%, 80% power was calculated. A futility stopping rule would halt random assignment if chemoconditioning was significantly inferior to TBI (EudraCT: 2012-003032-22; ClinicalTrials.gov: NCT01949129 ). RESULTS: Between April 2013 and December 2018, 543 patients were screened, 417 were randomly assigned, 212 received TBI, and 201 received chemoconditioning. The stopping rule was applied on March 31, 2019. The median follow-up was 2.1 years. In the intention-to-treat population, 2-year overall survival (OS) was significantly higher following TBI (0.91; 95% CI, 0.86 to 0.95; P < .0001) versus chemoconditioning (0.75; 95% CI, 0.67 to 0.81). Two-year cumulative incidence of relapse and treatment-related mortality were 0.12 (95% CI, 0.08 to 0.17; P < .0001) and 0.02 (95% CI, < 0.01 to 0.05; P = .0269) following TBI and 0.33 (95% CI, 0.25 to 0.40) and 0.09 (95% CI, 0.05 to 0.14) following chemoconditioning, respectively. CONCLUSION: Improved OS and lower relapse risk were observed following TBI plus etoposide compared with chemoconditioning. We therefore recommend TBI plus etoposide for patients > 4 years old with high-risk ALL undergoing allogeneic HSCT.